Development of a Contact Process Demonstration Tool n the Production of Sulfuric Acid to Improve Students' Learning Motivation on Chemical Equilibrium Concepts - Syakur, Ahmad; Paristiowati, Maria; Afrizal, Afrizal (International Journal of STEM Education for Sustainability, 2025)
This study aimed to; (1) develop a teaching aid for the contact process of sulfuric acid production in chemical equilibrium materials; (2) to find out the influence of contact process teaching aids on increasing learning motivation. This study used a mixed-method research design with product development using RD methods (Research and Development) using ADDIE (Analyze, Design, Development, Implement, Evaluation) model of product implementation and used a quasi-experimental method to test the effectiveness of the product. The contact process props are in the form of four sets of tools consisting of reactor 1 as a place for oxygen production, reactor 2 as a place for SO2 production, a balance shift pipe as a place for SO3 production, and SO3 Absorption as a place where SO3 meets H2O to produce H2SO4. Contact process props provide students with visualizations of shifts in chemical equilibrium affected by pressure and volume. The feasibility test of material and language experts was 88.44% and the media feasibility test of 91.33% showed that contact process teaching aids on chemical equilibrium materials are very feasible as practicum media. The results of the independent t-test stated that there was an influence of the product on learning motivation with a significance value of  0.012. Contact process teaching aids provide learning with macroscopic representations to students, thus making learning about chemical equilibrium material interesting.